Cardiopulmonary Demand of 16-kg Kettlebell Snatches in Simulated Girevoy Sport. Issue 6 (June 2020) - Chan, Margaux; MacInnis, Martin J.; Koch, Sarah; MacLeod, Kristin E.; Lohse, Keith R.; Gallo, Maria E.; Sheel, A. William; Koehle, Michael S.
Abstract : Abstract: Chan, M, MacInnis, MJ, Koch, S, MacLeod, KE, Lohse, KR, Gallo, ME, Sheel, AW, and Koehle, MS. Cardiopulmonary demand of 16-kg kettlebell snatches in simulated Girevoy Sport. J Strength Cond Res 34(6): 1625–1633, 2020—Kettlebell lifting has become popular both as a strength and conditioning training tool and as a sport in and of itself: Girevoy Sport (GS). Although several kettlebell multimovement protocols have been analyzed, little research has attempted to quantify the aerobic stimulus of the individual events in GS, which could better inform kettlebell-related exercise prescription. The purpose of this study was to quantify the cardiopulmonary demand, assessed primarily by oxygen consumption (V[Combining Dot Above]O2 ) and heart rate (HR), of continuous high-intensity kettlebell snatches—under conditions relevant to GS—and to compare this demand with a more traditional graded rowing ergometer maximal exercise test. Ten male participants (age = 28.4 ± 4.6 years, height = 185 ± 7 cm, body mass = 95.1 ± 14.9 kg) completed (a) a graded-exercise test on a rowing ergometer to determine maximal oxygen consumption (V[Combining Dot Above]O2 max) and maximal heart rate (HRmax) and (b) a graded-exercise test consisting of continuous 16-kg kettlebell snatches to determine peak oxygen consumption (V[Combining Dot Above]O2 peak) and peak heart rate (HRpeak) during a simulated GS snatch event. Subjects achieved a V[Combining Dot Above]O2 max of 45.7 ± 6.7 ml·kg −1 ·min −1 and HRmax of 177 ± 8.3 b·min –1 on the rowing ergometer. The kettlebell snatch test produced a V[Combining Dot Above]O2 peak of 37.6 ± 4.4 ml·kg −1 ·min −1 (82.7 ± 6.5% V[Combining Dot Above]O2 max) and a HRpeak of 174 ± 10 b·min –1 (98.0 ± 3.4% HRmax). These findings suggest that GS kettlebell snatches with 16-kg can provide an adequate aerobic stimulus to improve cardiorespiratory fitness in those with a V[Combining Dot Above]O2 max of ⩽51 ml·kg −1 ·min −1, according to aerobic training recommendations from the American College of Sports Medicine.